PsycEXTRA Dataset 2008
DOI: 10.1037/e620072009-001
|View full text |Cite
|
Sign up to set email alerts
|

Test Track and Driving Simulator Evaluations of Warnings to Prevent Right-Angle Crashes at Signalized Intersections

Abstract: This document is disseminated under the sponsorship of the U.S. Department of Transportation in the interest of information exchange. The U.S. Government assumes no liability for its contents or use thereof. This report does not constitute a standard, specification, or regulation. The U.S. Government does not endorse products or manufacturers. Trade and manufacturers' names appear in this report only because they are considered essential to the object of the document. Quality Assurance Statement The Federal Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…It is reasonable to expect that response times will be shorter as the available stopping distance decreases. In fact, this is what Inman et al reported in their analysis of the times of the brake response to the onset of amber in a test track environment (20). Their data suggest a 0.3-to 0.5-s difference in response time with a 75-ft (23-m) change in the distance from the stop line.…”
Section: Discussion Of Resultssupporting
confidence: 54%
“…It is reasonable to expect that response times will be shorter as the available stopping distance decreases. In fact, this is what Inman et al reported in their analysis of the times of the brake response to the onset of amber in a test track environment (20). Their data suggest a 0.3-to 0.5-s difference in response time with a 75-ft (23-m) change in the distance from the stop line.…”
Section: Discussion Of Resultssupporting
confidence: 54%
“…Driving simulators have been used to provide input for a variety of roadway design issues in Europe for some time (Keith et al, 2005) and the U.S. has begun to use simulators more widely for this purpose. Recent Federal Highway Administration (FHWA) projects have used simulators to investigate traffic calming in small towns (Molino, Katz, Hermosillo, Dagnall, & Kennedy, 2010), enhancement of visibility of curves on rural roads (Molino et al, 2010), driver response to a diverging diamond interchange (Federal Highway Administration, 2007), and driver response to warning of an approaching red-light violator (Inman, Davis, El-Shawarby, & Rakha, 2008). In addition, FHWA is currently funding a large project about making simulators more useful for human factors research (Federal Highway Administration, 2010).…”
Section: Driving Simulators For Work Zone Researchmentioning
confidence: 99%
“…Researchers suggest that the differences could be attributed to the participants recognizing a pattern in the real environment. Participants may have anticipated that the light would turn yellow as it had 20 out of the 24 times that participants approached the intersection (Inman et al, 2008).…”
Section: Semi-immersive Virtual Environments In a Transportation Settingmentioning
confidence: 99%